Intragroup Emotions: Physiological Linkage and Social Presence - Järvelä, Simo; Kätsyri, Jari; Ravaja, Niklas; Chanel, Guillaume; Henttonen, Pentti (Frontiers in Psychology, 2016)
We investigated how technologically mediating two different components of emotion – communicative expression and physiological state – to group members affects physiological linkage and self-reported feelings in a small group during video viewing. In different conditions the availability of second screen text chat (communicative expression) and visualization of group level physiological heart rates and their dyadic linkage (physiology) was varied. Within this four person group two participants formed a physically co-located dyad and the other two were individually situated in two separate rooms. We found that text chat always increased heart rate synchrony but HR visualization only with non-co-located dyads. We also found that physiological linkage was strongly connected to self-reported social presence. The results encourage further exploration of the possibilities of sharing group member’s physiological components of emotion by technological means to enhance mediated communication and strengthen social presence.